PEMANFAATAN MEDIA PEMBELAJARAN VIDEO DALAM PEMBELAJARAN MATERI TEPID SPONGE - Gusti Barlia Gusti; Wiradianto Putro (HealthCare Nursing Journal, 2022)
Learning is carried out in various ways, is very necessary to have technical variations of learning carried out on students so that the learning objectives that have been set can be achieved in accordance with the learning achievement criteria contained in the curriculum. Audiovisual learning using video is one of the techniques that can be done by utilizing existing video facilities. The long-term goal of this research is to serve as an effective and adaptive learning model for application in study groups. This study used a quasi-experimental pre-test and post-test design with control group. This study used purposive sampling. Analysis of the data used in this study is the Wilcoxon test for data that is not normally distributed for knowledge about video learning of the Tepid Sponge. The expected output in this study is the publication of scientific articles related to the use of the Tepid Sponge learning video in the learning process for nursing students. The results of the Wilcoxon test showed that there was a p value of 0.000 (so learning was declared effective) and continued by conducting the Mann Withney different test, it was found that learning using video was more effective.